Array - Bumi, Bunga Flamboyan Amara; Abdillah, Autar (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
In this article, we delve into the character of Sweeney Todd in the script of the drama "Sweeney Todd: The Hideous Shaver of Fleet Street" through the lens of literary psychology. Utilizing a source triangulation approach, especially combining various library sources, we explore the background, motives, and inner conflicts that make up the complexity of the main characters. The results of the analysis showed that Sweeney Todd's psyche was formed by a number of factors, including traumatic experiences, social injustice, and strong impulses. In addition, this article considers the relationship of these characters to the social and cultural contexts that influence them, taking into account the various viewpoints reflected in the literature sources. This approach provides a deeper insight into the characters and the literary work as a whole. As such, this analysis not only provides a deep understanding of Sweeney Todd's complexity, but also highlights the importance of source triangulation in unraveling literary works. It is hoped that a deeper understanding of this character can provide a broader view of the human condition in general. Keywords: psychiatric conditions, Sweeney Todd, literary psychology